Percy Jackson & the Olympians the lightning thief - Columbus, Chris; Rosenfelt, Karen; Barnathan, Michael; Radcliffe, Mark, 1952-; Hammel, Thomas M.; Mooradian, Greg; Morgan, Mark (Mark Paul); Oseary, Guy; Titley, Craig; Lerman, Logan, 1992-; Jackson, Brandon T., 1984-; Daddario, Alexandra, 1986-; et al. (Beverly Hills, CA 20th Century Fox Home Entertainment, 2010)
Percy Jackson is no ordinary teenager, he's the son of Poseidon and is accused of stealing Zeus' lightning bolt, the most powerful weapon ever created! With storm clouds brewing, Percy embarks on an incredible cross-country journey to prove his innocence, recover the bolt, and prevent a war among the gods that could destroy our world!
Originally produced as a motion picture in 2010.
Based on the novel by Rick Riordan.
Widescreen 2.35:1.
Special features: 5 deleted scenes; Discover your powers quiz; "The book comes to life" featurette.
Director of photography, Stephen Goldblatt ; costume designer, Renee April ; music by Christophe Beck ; visual effects supervisor, Kevin Mack ; edited by Peter Honess ; production designer, Howard Cummings ; executive producers, Thomas M. Hammel, Greg Mooradian, Guy Oseary, Mark Morgan.
Logan Lerman, Brandon T. Jackson, Alexandra Daddario, Jake Abel, Sean Bean, Pierce Brosnan, Steve Coogan, Rosario Dawson, Melina Kanakaredes, Catherine Keener, Kevin McKidd, Joe Pantoliano, Uma Thurman.
Keywords: Jackson, Percy -- (Fictitious character) -- Drama; Zeus -- (Greek deity) -- Drama; Teenagers -- Conduct of life -- Drama; Gods, Greek -- Drama; Malicious accusation -- Drama; Closed caption video recordings; Videodiscs; Video recordings for the visually handicapped; Fantasy films -- Juvenile; Action and adventure films -- Juvenile; Feature films -- Juvenile; Video recordings for the hearing impaired -- Juvenile; Video recordings for people with visual disabilities -- Juvenile; Film adaptations; Drama